Combined Swingletree and Evener. - White, Floyd N. (United States. Patent Office., 1920)
Patent, including illustrations, for improvements to combined swingletrees and eveners, tools used to equalize strain between a draft animal and vehicle, "which is easily and simply constructed, inexpensive to manufacture, and one which will be very efficient in operation" (lines 22-25).